Algebraic Methods for Proving Geometric Theorems - Dhiman, Neeraj (International Journal of Control and Automation, 2018)
Successful algebraic approaches for theorem proving in mechanical geometry have been developed in the previous decade. The use of algebraic techniques for the proof of geometric theorems automatically is the subject of this article. Research into algorithmically proving geometric propositions is important for the development of robots and AI. We give a straightforward Maple implementation of these methods and use it to establish a few elementary geometry truths.